THE EFFECT OF ONLINE LEARNING (WHATSAPP) AND STUDENTS INDEPENDENT ON THE LEARNING OUTCOME OF SOCIOLOGY AT SMAN 1 KUPANG - Yanuaria Marsela Nahak (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2022)
The purpose of this study was to determine the effect of WhatsApp Online Learning Media and the outcome of student independence Learning at SMA Negeri 1 Kupang. The location of this research was SMA Negeri Kupang. The informant determination technique used was purposive sampling. Informants in this study were students of class X SMA Negeri 1 Kupang. This research uses several techniques such as questionnaires and documentation. The data technique in this research is the validity test and the rehabilitation test. The data analysis stage begins with validity and reliability tests and continues with descriptive analysis and inferential statistical analysis consisting of classical assumption tests, multiple linear regression analysis, statistical hypothesis testing, determination of correlation coefficient values, and determination of the coefficient of determination (R2). The results of this study conclude that WhatsApp online learning media and student independence have a positive and significant influence on sociology learning outcomes of class X at SMA Negeri 1 Kupang. This is evidenced by the test results, where the significance value of the WhatsApp online learning media variable (X1) and student independence (X2) is 0.000 or less than the alpha level used, which is 0.05 (5%).